The importance of communication skills required to reduce set-up errors in the radiotherapy planning phase. Issue 4 (21st December 2019) - Merlotti, A.; Reali, A.; Russi, E.
Abstract: During the planning computed tomography (CT) scan, patients experience the position and any immobilisation technique required for radiotherapy. Patient's stress and anxiety can cause muscle tension that can introduce systematic set-up errors if not recognised and corrected. We discuss two clinical cases that highlight the importance of time dedicated to communication and revision of the first CT acquisition during a virtual simulation procedure.